2017
DOI: 10.1007/978-3-319-53889-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Drug Addiction and DNA Modifications

Abstract: Drug addiction is a complex disorder which can be influenced by both genetic and environmental factors. Research has shown that epigenetic modifications can translate environmental signals into changes in gene expression, suggesting that epigenetic changes may underlie the causes and possibly treatment of substance use disorders. This chapter will focus on epigenetic modifications to DNA, which include DNA methylation and several recently defined additional DNA epigenetic changes. We will discuss the functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 103 publications
1
19
0
2
Order By: Relevance
“…For more than a decade, the effects of drugs of abuse in the central nervous system have been shown to involve epigenetic changes on either histones or DNA . Concerning ethanol (EtOH), for example, a study showed in 2004 that chronic EtOH exposure increases expression of the GluN2B NMDA receptor subunit in cortical neurons through DNA demethylation .…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, the effects of drugs of abuse in the central nervous system have been shown to involve epigenetic changes on either histones or DNA . Concerning ethanol (EtOH), for example, a study showed in 2004 that chronic EtOH exposure increases expression of the GluN2B NMDA receptor subunit in cortical neurons through DNA demethylation .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on rodents have proposed that prenatal alcohol exposure can give rise to epigenetic modifications ( Perkins et al 2013 ; Brown and Feng 2017 ; Chater-Diehl et al 2017 ; Tulisiak et al 2017 ). Future studies in Drosophila can assess whether prenatal alcohol exposure results in histone modifications that drive altered gene expression and, if so, to what extent such modifications persist across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Instead it is likely that certain dietary factors alter endophenotypes that are relevant to a spectrum of mental illnesses. For instance, DNA methylation is affected in MDD, but also in drug addiction (Brown and Feng, 2017) and Alzheimer's disease (Qazi et al, 2018). Hence, altering the one-carbon metabolism through vitamins B9 and B12 may change the symptomology for all of these conditions.…”
Section: Conclusion -Nutrition An Depression: Researchers Still Have mentioning
confidence: 99%